Pengembangan SmartStat Web berbasis problem based learning pada materi statistika untuk meningkatkan kemampuan berpikir kritis matematis - Resa Anggraeni; Euis Eti Rohaeti; Risma Amelia (IKIP Siliwangi, 2026)
This reseacrh aims to develop SmartStat Web based on Problem Based Learning and test its effectiveness in improving students' mathematical critical thinking skills. The study used the Research and Development (R&D) method with the ADDIE model. The research subjects consisted of 6 students in one-to-one trials, 25 students in small-group trials, 22 students in field trials, and 22 students in each experimental and control class. Data were collected through validation sheets, observations, interviews, response questionnaires, and mathematical critical thinking ability tests. The results showed that SmartStat Web was very valid with a percentage of 92.17% in the media aspect and 88% in the material aspect, and very practical with a percentage of 85.25%, 87.70%, and 88.20% at each trial stage. The media was also proven effective with an N-Gain value of 0.78 in the experimental class which was higher than the control class at 0.60 and the t-test results showed a significant difference. Thus, SmartStat Web based on Problem Based Learning is declared valid, practical, and effective in improving students' mathematical critical thinking skills.